RIFM fragrance ingredient safety assessment, methyl ionone (mixture of isomers), CAS registry number 1335-46-2. (December 2019) - Api, A.M.; Belsito, D.; Biserta, S.; Botelho, D.; Bruze, M.; Burton, G.A.; Buschmann, J.; Cancellieri, M.A.; Dagli, M.L.; Date, M.; Dekant, W.; Deodhar, C.; et al.
Abstract: Methyl ionone (mixture of isomers) was evaluated for genotoxicity, repeated dose toxicity, developmental and reproductive toxicity, local respiratory toxicity, phototoxicity/photoallergenicity, skin sensitization, and environmental safety. Data from methyl ionone (mixture of isomers) show that the material is not genotoxic and provided a NESIL of 70, 000 μg/cm 2 for the skin sensitization endpoint. Data provided a calculated MOE >100 for the repeated dose toxicity and developmental toxicity endpoints, and data from read-across material (E)-β-ionone (CAS # 79-77-6) provided a calculated MOE >100 for the reproductive toxicity endpoint. For the local respiratory endpoint, a calculated MOE >100 was provided by the read-across material β-ionone (CAS # 14901-07-6). The phototoxicity/photoallergenicity endpoints were evaluated based on data and UV spectra; the material is not phototoxic/photoallergenic. The environmental endpoints were evaluated with data from the target chemical and read-across material α-allylionone (CAS # 79-78-7), and the material was not found to be PBT; its risk quotients, based on current volume of use in Europe and North America (PEC/PNEC), are <1. Highlights: Methyl ionone (mixture of isomers); a safety assessment based on RIFM's criteria. A safety assessment based on 7 human health endpoints plus environmental. All endpoints were cleared using target data, read-across, and/or TTC.